Vascular smooth muscle cells in intimal hyperplasia, an update - Déglise, Sébastien; Bechelli, Clémence; Allagnat, Florent (Frontiers in Physiology, 2023)
Arterial occlusive disease is the leading cause of death in Western countries. Core contemporary therapies for this disease include angioplasties, stents, endarterectomies and bypass surgery. However, these treatments suffer from high failure rates due to re-occlusive vascular wall adaptations and restenosis. Restenosis following vascular surgery is largely due to intimal hyperplasia (IH). IH develops in response to vessel injury, leading to inflammation, vascular smooth muscle cells dedifferentiation, migration, proliferation and secretion of extra-cellular matrix into the vessel’s innermost layer or intima. In this review, we describe the current state of knowledge on the origin and mechanisms underlying the dysregulated proliferation of vascular smooth muscle cells in IH, and we present the new avenues of research targeting VSMC phenotype and proliferation.